(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article considers the main factors of natural-climatic and environmental. Taking into account the influence of these factors on the planning structure of urban-type settlements is the main development of the principles of structural and planning organization of settlements that have transformed the status of urban-type settlements in Uzbekistan.